Genome-wide estimation of inbreeding coefficient, effective population size and haplotype blocks in Vrindavani crossbred cattle strain of India. Issue 5 (28th May 2021) - Chhotaray, Supriya; Panigrahi, Manjit; Pal, Dhan; Ahmad, Sheikh Firdous; Bhanuprakash, V.; Kumar, Harshit; Parida, Subhashree; Bhushan, Bharat; Gaur, G. K.; Mishra, B. P.; Singh, R. K.
ABSTRACT: In the present study, to analyze the genomic ROH fragments, haplotypes, inbreeding coefficient and effective population size (N e ), SNP50K data of 72 Vrindavani crossbred cattle strain were obtained. After a quality check, 24, 449 biallelic SNPs were retained, which were in HWE, MAF > 0.01 and genotyping rate >95%. A total of 385 ROH were found, and chromosome 25 was mostly covered with 50.86%, while chromosome one was least with 12.42%. We classified ROH into <10Mb, 10-15Mb, 15-20Mb, >20Mb categories and observed a 3% inbreeding coefficient for the population in >20Mb category. Inbreeding from an excess of homozygosity was found to be 6% in the population. Ne was also estimated through N e Estimator and SNeP and in the recent generation, it was found to be 40 for a census size of 464 cattle. The Ne /Nc ratio was found to be 0.086 and a decreasing trend of Ne was observed for over five generations. 45.95% of the autosomal genome was covered with haplotypic structure with highest total block length in chromosome one and lowest in 28. From all the observations made in this study, it can be concluded that Vrindavani is an admixed cattle strain but have an unstable population structure in the current period.